2017
DOI: 10.3390/sports5040088
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Relationship between Lying and Standing Ultrasonography Measures of Muscle Morphology with Isometric and Dynamic Force Production Capabilities

Abstract: The purpose of the current study was (1) to examine the differences between standing and lying measures of vastus lateralis (VL), muscle thickness (MT), pennation angle (PA), and cross-sectional area (CSA) using ultrasonography; and (2) to explore the relationships between lying and standing measures with isometric and dynamic assessments of force production—specifically peak force, rate of force development (RFD), impulse, and one-repetition maximum back squat. Fourteen resistance-trained subjects (age = 26.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 51 publications
(75 reference statements)
1
25
4
Order By: Relevance
“…Wagle et al [15] reported stronger relationships between standing measures of muscle size and isometric variables compared to supine measures, however, in the current study, no measures of muscle size were significantly related to any of the isometric variables. This may be a result of a discrepancy between positions, as the ultrasound assessments were completed while in the recumbent position or while standing and the isometric tests were completed while seated.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Wagle et al [15] reported stronger relationships between standing measures of muscle size and isometric variables compared to supine measures, however, in the current study, no measures of muscle size were significantly related to any of the isometric variables. This may be a result of a discrepancy between positions, as the ultrasound assessments were completed while in the recumbent position or while standing and the isometric tests were completed while seated.…”
Section: Discussioncontrasting
confidence: 86%
“…Muscle morphology measured in the IP position appears to be best related to physical performance, although utilizing the NDLR and DLR positions may provide comparable results. Although standing measures of VL morphology have previously been reported to exhibit stronger relationships with performance than recumbent measures [15], our results suggest that the relationship between muscle morphology and performance in ST may be weaker compared to the recumbent positions.…”
Section: Discussioncontrasting
confidence: 70%
“…Finally, in the present study, RFD was evaluated in testing positions that were different to the ultrasound collection position. Recent study report that performing ultrasonography evaluation of vastus lateris architecture with athletes in a lying position or in a different position when compared to those that they have during strength and power evaluations, does not allow for us to have a precise view of muscle configuration that is present during performance evaluations, and this may have some impact on the correlations between strength/power performances and architecture parameters [18]. Unfortunately, the present study performed prior to this report.…”
Section: Discussioncontrasting
confidence: 42%
“…Previous studies indicate that pennation angle and muscle thickness seems to affect late RFD [2,14,17,18]. Fascicle length is thought to reflect the number of sarcomeres in series in a muscle and the increase in this number has been suggested to contribute to higher shortening velocity and muscle power [19].…”
Section: Introductionmentioning
confidence: 99%
“…Even though athletes served as their own control, it is possible that athletes replenish glycogen content differently if nutrition (i.e., strategic ingestion of carbohydrates and proteins) and hydration (i.e., strategic ingestion of water and sports drinks) protocols are adequate and controlled throughout the day. Additionally, ultrasound assessments of glycogen content scores may be influenced by muscle size, postural alignment [ 26 ], and even ultrasound transducer pressure. While the current standard for assessing glycogen content within a muscle is to obtain muscle biopsies, this technique was not feasible during the preseason.…”
Section: Discussionmentioning
confidence: 99%